Formulation of Lip Balm from Nanoparticles of Beetroot Extract (Beta vulgaris L) and Testing of Sunscreen Activity - Nabila Meilani Dewi; Senda Kartika Rakainsa (Journal of Science and Technology Research for Pharmacy, 2025)
Background: As a tropical country, Indonesia faces the risk of skin damage due to year-round sun exposure, including on the lips, which are susceptible to UV effects such as dryness, cracking, and hyperpigmentation. This study utilizes the betacyanin content in beetroot (Beta vulgaris L.)—a phenolic compound with photoprotective properties that can counteract UV free radicals. This study applies nanotechnology through the formulation of beetroot extract nanoparticles to optimize sunscreen activity. Aim: This study aims to evaluate and compare the sunscreen activity between lip balm formulations containing beetroot extract nanoparticles and beetroot extract lip balm formulations, as well as to determine the extent of the effectiveness of nanoparticle-based lip balm in providing protection against UV rays. Materials and Methods: This study extracted beetroot (Beta vulgaris L.) using the maceration method with 96% ethanol, yielding a concentrated extract (yield 34%) with a dark red color. Results: Phytochemical analysis revealed the presence of flavonoids, phenolics (20 mg GAE/g), tannins, and alkaloids in beetroot. The nanoparticle extract was successfully formulated with a size of 1.05 nm (PDI 0.403) and a zeta potential of -21.0 mV. Among the seven lip balm formulations, F6 (30% nanoextract) demonstrated the best performance with an SPF of 25.25 (ultra category), %Te of 0.26%, and %Tp of 0.61%, as well as optimal physical stability (homogeneous, melting point 70°C, pH 4.5–6.5). The nanoextract formulas (F4–F6) significantly outperformed conventional extracts (F1–F3) in sunscreen activity, demonstrating the effectiveness of nanotechnology in enhancing UV protection. Conclusion: These findings demonstrate that beetroot nanoparticle extracts have potential as an effective and safe natural sunscreen lip balm for lip protection